Changes in internal resistance of lithium-sulfur batteries when using electrolytes based on ionic liquid [DEME][TFSI], sulfolane or TEGDME solvent - Drvarič Talian, Sara; Dominko, Robert (Anali PAZU, 2022)
Internal resistance of lithium-sulfur batteries was investigated with impedance spectroscopy. In order to understand the effect of various common solvents for Li-S battery preparation, the electrolyte in the cells was varied (ionic liquid [DEME][TFSI], sulfolane or TEGDME solvent). The impedance changes were followed at several points during discharge and charge of the batteries and through 50 cycles of their use. The resulting spectra were analyzed and fitted, extracting information on four different impedance contribution. The contributions were assigned to the electrolyte, anode or cathode. Their change through a single cycle and through multiples cycles of battery use was evaluated as well as compared between cells employing different electrolytes.
Keywords: lithium-sulfur batteries; polysulfides; impedance spectroscopy; ionic liquid; electrolytes